Burkina Faso : Third Review under the Extended Credit Facility Arrangement-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Burkina Faso's Third Review Under the Extended Credit Facility (ECF) Arrangement. Policies and reform implementation under the ECF-supported program have been satisfactory. All end-June 2019 quantitative performance criteria and indicative targets were met as well as all, but one, structural benchmarks throughout end-November 2019. Notwithstanding security challenges, economic growth remains resilient and is expected to stabilize at 6 percent in 2019 and over the medium term. Inflation is expected to be negative in 2019, owing to food price deflation following recent good harvests, and to rebound in 2020. However, the security crisis poses risks to the growth outlook and to the authorities' reform agenda. Reforms to curb wage bill growth are advancing in some areas, including the implementation of transitional measures to help bring down the wage bill relative to tax revenues. However, progress toward the adoption of the overall reform package is limited. Pending approval of this overall reform package, the authorities are committed to refrain from any new agreements on wages or allowances outside of the security sector.